2022
DOI: 10.31083/j.fbl2710285
|View full text |Cite
|
Sign up to set email alerts
|

Natural Biologics Accelerate Healing of Diabetic Foot Ulcers by Regulating Oxidative Stress

Abstract: Difficult or even non-healing diabetic foot ulcers (DFU) are a global medical challenge. Although current treatments such as debridement, offloading, and infection control have resulted in partial improvement in DFU, the incidence, amputation, and mortality rates of DFU remain high. Therefore, there is an urgent need to find new or more effective drugs. Numerous studies have shown that oxidative stress plays an important role in the pathophysiology of DFU. The nuclear factor erythroid 2-related factor (Nrf2) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 153 publications
0
5
0
Order By: Relevance
“…Numerous studies have attempted to highlight the role of ROS in delayed wound healing: the impairment of redox homeostasis due to increased production of ROS induces oxidative damage at the cellular level, which inhibits wound healing [23,24]. Moreover, the Nuclear factor (erythroid-derived 2)-like 2 (Nrf2) signaling pathway, involved in the transcription of antioxidant genes, is also impacted in diabetes [25]. It is, therefore, oxidative stress, which represents an increase in the level of ROS and/or a decrease in antioxidant defenses [22], which is involved when the healing defect [26].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have attempted to highlight the role of ROS in delayed wound healing: the impairment of redox homeostasis due to increased production of ROS induces oxidative damage at the cellular level, which inhibits wound healing [23,24]. Moreover, the Nuclear factor (erythroid-derived 2)-like 2 (Nrf2) signaling pathway, involved in the transcription of antioxidant genes, is also impacted in diabetes [25]. It is, therefore, oxidative stress, which represents an increase in the level of ROS and/or a decrease in antioxidant defenses [22], which is involved when the healing defect [26].…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis also demonstrated that the key genes identified were mainly related to the keratinization and differentiation of skin cells and inflammatory pathway-related receptors such as rage receptor binding and TLR4 receptor binding. On the one hand, the physiological environment of hyperglycemia in diabetic patients stimulates the AGE-RAGE pathway, thus triggering a persistent inflammatory response that inhibits the healing of ulcers in DFU patients (Song et al, 2022). The inflammatory damage caused by oxidative stress and the AGEs-RAGE pathway has also been detected in CLE patients (Martens et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…At this stage, the expression of anti-inflammatory markers, such as interleukin-12 (IL-12), IL-6, IL-1 or tumor necrosis factor-α, is enhanced, while the activity of anti-inflammatory cues, such as IL-10 and IL-4, is reduced [ 7 , 12 ]. This leads to an imbalance between angiogenic factors (promoters of new blood vessel formation) and angiostatic factors, impairing angiogenesis and leading to endothelial progenitor cell dysfunction aside from hindering the proliferation and migration of fibroblasts and keratinocytes [ 10 , 13 ]. This is exacerbated by the limited neuropeptide activity at the site, since in hyperglycemia conditions, neuropeptides such as Substance P, neuropeptide Y or neurotensin endowed with regenerative functions, have their activity reduced.…”
Section: Diabetic Ulcers: Healing Impairments and Classificationsmentioning
confidence: 99%